REE SYSTEMATICS AND ND MODEL AGE OF UPPER VENDIAN ARGILLITES OF THE SHKAPOVO-SHIKHAN DEPRESSION - Maslov A.V.; Ronkin Yu.L.; Lepikhina O.P.; Isherskaya M.V. (My University, 2006)
The Shakapovo–Shikhan Depression—one of the largest in the eastern part of the East European Platform—is filled with Upper Vendian sedimentary rocks of the Bizhbulyak Complex about 1.6–1.8 km in total thickness. The depression is framed by the Orenburg, Tatar, and Komi–Permyak arches in the southwest, west, and northwest, respectively. These arches are composed of the Archean (~80% of total area of ancient drainage basin) and Paleoproterozoic crystalline rocks.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский